2007
DOI: 10.1159/000107552
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Statins on the Progression of Atherosclerotic Renovascular Disease

Abstract: Background/Aims: The aim was to examine the influence of statin therapy on the natural history of atherosclerotic renal artery stenosis (RAS). Methods: Our hospital atherosclerotic renovascular disease (ARVD) database was analysed for patients who underwent repeat renal angiography during clinical follow-up. Patients with ≧1 RAS lesion and ≧4 months between baseline and repeat renal angiography were analysed. 79 patients were included. Baseline renal arterial anatomy was classified as normal, ≤50% RAS, >50% RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 35 publications
1
39
0
1
Order By: Relevance
“…Other studies have shown increased levels of free-fatty acids (glycerol-glyceride) in patients with ARVD [ 48 ], though this may have more important implications for mortality than development of atheroma [ 49 ]. However, intervention with statins has been shown to prevent anatomical progression of RAS in a retrospective study, which provides some support to the pathogenic effect of hypercholesterolemia in renal atherogenesis [ 50 ].…”
Section: Hyperlipidemiamentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies have shown increased levels of free-fatty acids (glycerol-glyceride) in patients with ARVD [ 48 ], though this may have more important implications for mortality than development of atheroma [ 49 ]. However, intervention with statins has been shown to prevent anatomical progression of RAS in a retrospective study, which provides some support to the pathogenic effect of hypercholesterolemia in renal atherogenesis [ 50 ].…”
Section: Hyperlipidemiamentioning
confidence: 93%
“…These fi gures are only of historical interest in the current era of statin therapy. Although available data are retrospective, in a study of 79 patients with ARVD, statin treated patients (n = 40) were much less likely to suffer progression of stenosis at 3-years (odds ratio 0.28, p = 0.01) than non-statin treated patients [ 50 ] (Fig. 1.2 ).…”
Section: Progression Of Stenosismentioning
confidence: 97%
“…Treatment with angiotensin blockade 23,24 and lipid-lowering therapy 25 is accepted as a minimum standard of care, and there is consensus that other vascular risk reduction measures should be applied. Given differences in medical therapy within and between published RCT data, direct comparison between studies is not practical.…”
Section: Medical Therapymentioning
confidence: 99%
“…a retrospective study of serial angiography has shown that the use of statins actually reduces the risk of progression of atherosclerotic ras. 16 another…”
Section: Natural Historymentioning
confidence: 99%